21st-Century Learning: Development of Respiradroid Media (Respiration Concept) For High School Students - Nurhalimah Nurhalimah; Elsa Lisanti; Rizhal Hendi Ristanto (Universitas Tidar, 2020)
This research is a research development that aims to develop biology learning media in the form of an android learning application. This study uses research and development (R&D) with a method developed by Thiagarajan, namely the 4D model with stages: define, design, develop and disseminate, the stages of this study are limited to the development stage. Products that have been developed are then validated by experts in their fields. The results showed that respiradroid learning media had an average of 3, 31 in aspects of learning media. The validation results obtained from media and material experts prove that respiradroid media developed are suitable for use in the learning process. Media respiradroid learning has the advantage that is, a learning media that is flexible means that it can be used anywhere, easy to install, easy to find material content with student stimulus for thinking. It is expected to improve students' higher-order thinking skills in the concept of respiration.